2011
DOI: 10.4172/1948-5956.1000058
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Phosphoethanolamine Induces Apoptosis Through Caspase-3 Pathway by Decreasing Expression of Bax/Bad Protein and Changes Cell Cycle in Melanoma

Abstract: Materials and Methods ChemicalAmino-ethyl phosphoric ester was prepared according to [9] with purity over 99% analyzed by High-performance liquid chromatography (HPLC). The stock solution 1M was dissolved in water and stored at room temperature for in vitro and in vivo test. Cell cultureB16F10 murine melanoma (CLR 6475) and human fibroblast (CCL-75) cell lines were obtained from the American Type Culture Collection (ATCC). B16F10 cells and fibroblasts were grown in RPMI-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
42

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 26 publications
3
51
1
42
Order By: Relevance
“…Follicular carcinoma is more common in women who are affected over a broad age range [21].Cancer is basically a cell disease, characterized by a loss in the mechanisms which drive the proliferation and cellular differentiation [22]. The cells were cultured and the proliferation was assessed by cell counting using a haemocytometer after trypsin digestion [23].…”
Section: Follicular Thyroid Cancermentioning
confidence: 99%
“…Follicular carcinoma is more common in women who are affected over a broad age range [21].Cancer is basically a cell disease, characterized by a loss in the mechanisms which drive the proliferation and cellular differentiation [22]. The cells were cultured and the proliferation was assessed by cell counting using a haemocytometer after trypsin digestion [23].…”
Section: Follicular Thyroid Cancermentioning
confidence: 99%
“…Dacarbazine is currently the only approved chemotherapy drug for the standard treatment of metastatic melanoma stage IV, but its therapeutic response is not satisfactory and only 15-20% of patients with favorable prognosis have increased survival rate [68].…”
Section: Drugsmentioning
confidence: 99%
“…2,3 In a recent report, we showed that synthetic phosphoethanolamine (PHO-S), an aminoethyl phosphoric ester, has a great potential to induce cell death in B16F10 (melanoma murine) cells and without apparent damage to normal cells, such as fibroblasts and lymphocytes. 4,5 We demonstrated that PHO-S is effective in the reduction of DNA…”
Section: Introductionmentioning
confidence: 97%
“…[4][5][6][7] The antineoplastic phospholipids are a new class of antitumor agents, which can cause collateral effects, such as gastrointestinal toxicity, hemolysis, and liver and renal dysfunction. These effects are attributed to agents such as edelfosine, ilmofosine, and miltefosine.…”
mentioning
confidence: 99%